Erratum: Comparative epidemiological analysis on two-batch study of breast cancer in Dr. Cipto Mangunkusumo Hospital, Jakarta - Indonesia (Faculty of Medicine Universitas Indonesia, 1999)
[This corrects the article DOI:Â 10.13181/mji.v8i2.682]